Answer:
B
Explanation:
Calculate the slope m using the slope formula and equate to
![(3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/810xodspel5mrswej0fay1vvz0sburw3kp.png)
m =
![(y_(2)-y_(1) )/(x_(2)-x_(1) )](https://img.qammunity.org/2021/formulas/mathematics/middle-school/89lni2arad82a9125nchkq0vkwnbj1bzli.png)
with (x₁, y₁ ) = (3, 2) and (x₂, y₂ ) = (r, - 4)
m =
=
, then equating gives
=
( cross- multiply )
3(r - 3) = - 12 ( divide both sides by 3 )
r - 3 = - 4 ( add 3 to both sides )
r = - 1 → B